PENGARUH KUALITAS LAPORAN KEUANGAN, PENYAJIAN LAPORAN KEUANGAN DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Hafzan Fikrian; Amir Hasan; Al Azhar A. ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to describe the influence of Quality of Financial Reporting, Financial Statements Effect, and Effect Against Accountability Accessibility Financial Statements of Financial Management At Work Unit of City of Pekanbaru. The population covers all aspects related to the preparation of financial statements in government agencies located in the city of Pekanbaru. The population in this study consisted of all SKPD contained in Pekanbaru city as much as 32 SKPD. Each SKPD will be spread as much as 3 questionnaire consisted of Chief SKPD, Head of Finance and Head of the planning of each SKPD contained in Pekanbaru, bringing the total respondents were 96 respondents. Further analysis of data using multiple regression analysis through SPSS 17.0 software msi. The result of the calculation as described is known that affect the quality of financial statements Financial Management Accountability. The result of the calculation as described can be seen that the effect on the financial statements of Financial Management Accountability. The result of the calculation as described can be seen that the effect on the accessibility of Financial Statements Financial Management Accountability in the SKPD Pekanbaru.Keywords: Quality, Presentation, Accessibility, and Accountability